Modulation effect of sulfated polysaccharide from Sargassum fusiforme on gut microbiota and their metabolites in vitro fermentation - Jiang, Long; Song, Chen; Ai, Chunqing; Wen, Chengrong; Song, Shuang (Frontiers in Nutrition, 2024)
The present study demonstrated the digestion behavior and fermentation characteristics of a sulfated polysaccharide from Sargassum fusiforme (SFSP) in the simulated digestion tract environment. The results showed that the molecular weight of two components in SFSP could not be changed by simulated digestion, and no free monosaccharide was produced. This indicates that most of SFSP can reach the colon as prototypes. During the fermentation with human intestinal flora in vitro, the highermolecular-weight component of SFSP was utilized, the total sugar content decreased by 13%, the reducing sugar content increased, and the galactose content in monosaccharide composition decreased relatively. This indicates that SFSP can be selectively utilized by human intestinal flora. At the same time, SFSP also changed the structure of intestinal flora. Compared with the blank group, SFSP significantly increased the abundance of Bacteroidetes and decreased the abundance of Firmicutes. At the genus level, the abundances of Bacteroides and Megamonas increased, while the abundances of Shigella, Klebsiella and Corinthians decreased. Moreover, the concentrations of total short-chain fatty acids (SCFAs), acetic, propionic and n-butyric acids significantly increased compared to the blank group. SFSP could down-regulate the contents of trimethylamine, piperidone and secondary bile acid in fermentation broth. The contents of nicotinic acid, pantothenic acid and other organic acids were increased. Therefore, SFSP shows significant potential to regulate gut microbiota and promote human health.